Analysis of The Impact of Revitalization of The Blok M Area on Business Growth And Local Economic Activity - Lazarus Sinaga; Erwin Permana; Elsa Rachmawati (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the impact of the revitalization of the Blok M area on urban economic dynamics through transportation integration and the development of creative public spaces. Using a qualitative method with a descriptive-analytical approach, this study examines the phenomenon of regional transformation after the integration of the transportation system and local economic activities through a literature review. The results show that the revitalization of Blok M has successfully transformed the previously stagnant area into a dynamic economic ecosystem. The application of the Transit-Oriented Development (TOD) concept significantly improves accessibility through the connectivity of the Jakarta MRT and TransJakarta. The increase in visitor flow (foot traffic) not only restores Blok M's function as a transportation hub but also makes it a relevant social destination for the younger generation. The emergence of economic agglomeration through the growth of new business units provides a multiplier effect on the local economy and empowers MSMEs. This revitalization contributes positively to the structure of DKI Jakarta's GRDP, especially in the trade sector and the provision of food and beverage accommodations. These findings confirm that an integrated urban regeneration strategy with mass public transportation is an important catalyst in driving sustainable urban economic growth.